Lipoenxertia autóloga periorbitária no rejuvenescimento facial: análise retrospectiva da eficácia e da segurança em 31 casos Autologous periorbital fat grafting in facial rejuvenation: a retrospective analysis of efficacy and safety in 31 cases - Chang Yung Chia; Diego Antonio Rovaris (Revista Brasileira de Cirurgia Plástica)
INTRODUÇÃO: Os sulcos periorbitários e zigomático e o malar flácido estão entre as características mais marcantes de envelhecimento ou de desarmonia facial. A reposição do volume é um método simples e eficiente, e o lipoenxerto pode ser o melhor material. O presente trabalho traz uma análise de 31 pacientes submetidos a autolipoenxertia, com ênfase na eficácia e na segurança da técnica. MÉTODO: Análise retrospectiva de 31 pacientes consecutivos, submetidos a lipoenxertias periorbitária e malar, concomitantemente ou não a outros procedimentos estéticos. A avaliação foi feita por meio de comparação entre fotografias pré e pós-operatória, bem como pelo grau de satisfação dos pacientes. RESULTADOS: Dos 31 pacientes, 26 (83,9%) classificaram o resultado pós-operatório como ótimo, 3 (9,7%), bom, e 2 (6,4%), regular. Na avaliação dos autores, 24 (77,5%) pacientes apresentaram resultado ótimo, 5 (16,1%), bom, e 2 (6,4%), regular. Houve necessidade de retoque de lipoenxertia em apenas 4 pacientes, por sugestão do cirurgião. As complicações foram mínimas e passageiras. CONCLUSÕES: A lipoenxertia facial é fácil e eficaz, e as complicações são mínimas quando realizada por cirurgiões qualificados. BACKGROUND: Periorbital and zygomatic hollows as well as flaccid cheeks are among the most evident characteristics of aging or facial disharmony. Volume replacement is a simple and efficient procedure, and fat grafting is considered as the best treatment for these characteristics. This study evaluates 31 patients who underwent autologous fat grafting and emphasizes the safety and efficacy of this procedure. METHODS: A retrospective analysis of 31 consecutive patients who underwent periorbital and zygomatic fat grafting, alone or in combination with other cosmetic procedures, was carried out. Final evaluation was performed by assessing pre- and postoperative photographs as well as the degree of patient satisfaction. RESULTS: Of 31 patients, 26 (83.9%) reported excellent postoperative outcomes; 3 (9.7%), satisfactory outcomes; and 2 (6.4%), poor outcomes. According to the authors' evaluation, 24 (77.5%) patients had excellent outcomes, 5 (16.1%) had satisfactory outcomes, and 2 (6.4%) had poor outcomes. Retouching of the fat graft was recommended for only 4 patients. The complications observed were minimal and transient. CONCLUSIONS: Facial fat grafting is a simple and effective procedure that presents minimal complications when performed by skilled surgeons.